IMPROVING STUDENTS’ READING COMPREHENSION OF THE TWELFTH GRADE STUDENTS OF SMA NEGERI 1 BATANG KUIS THROUGH GROUP INVESTIGATION METHOD - Sinurat, Torang Maruli; Sari, Anna Stasya Prima; Sembiring, Novalina (Kairos English Language Teaching Journal, 2017)
Reading is not only about pronouncing written words correctly but also comprehending the text. It is not surprising that students have difficulties in reading comprehension. For example: Students cannot understand and share information of the text. Thus, there must be a method which can help them read effectively. Group Investigation method can help improve the students’ reading comprehension and motivation to read. The objectives of this research are to find out that Group Investigation method improves students’ reading comprehension and to describe the students’ responses towards learning teaching process of reading comprehension through the application of Group Investigation method. This research is Classroom Action Research (CAR) which was conducted by applying Group Investigation method to the twelfth grade students of SMA Negeri 1 Batang Kuis. After six meetings, it could be seen that there is a significant improvement of the students’ reading comprehension. The results of the tests showed that the students’ mean score in the pretest is 60.25 with 15.62% of the students who got score > 75, the students’ mean score in the formative test is 71.25 with 28.12% of the students who got score > 75, and the students’ mean score in the posttest is 78.87 with 71.87% of the students who got score > 75. The quantitative data analysis showed that there is a significant mean score increase from pretest to posttest, namely about 56.25%. The qualitative data analysis showed that the students’ responses towards the application of Group Investigation method in the learning teaching processes of reading comprehension on narrative texts are very positive. They agree that the application of Group Investigation method could help them improve their reading comprehension. It is suggested that English teachers apply Group Investigation method as an alternative to improve their students’ reading comprehension.